Association of APOA5 -1131T>C polymorphism with obesity in coronary artery disease - Çoban, Neslihan (Turk Kardiyoloji Dernegi arsivi : Turk Kardiyoloji Derneginin yayin organidir, 2020)
Genetic risk factors that cause coronary artery disease (CAD) demonstrate variations in different populations. In this study, a single nucleotide polymorphism in the APOA5 gene was targeted to determine genetic contributors to atherosclerotic CAD. The effects of this polymorphism on the development of CAD and known risk factors of the disease were examined. A total of 448 patients with angina or acute myocardial infarction who underwent coronary angiography were grouped as individuals with normal coronary arteries (≤30% stenosis) and critical disease (≥50% stenosis). The angiographic severity and the extent of atherosclerotic CAD were assessed using the Gensini and SYNTAX scores. Individuals were genotyped for the APOA5-1131T>C polymorphism using hydrolysis probes and the results were evaluated. The APOA5-1131T>C polymorphism was associated with the serum lipid levels in the non-CAD group (p<0.05). In addition, the effect of APOA5 gene polymorphism on clinical status and other parameters was determined to vary depending on gender. A borderline association was found between APOA5 -1131T>C and type 2 diabetes mellitus (p=0.055). This polymorphism was found to be associated with obesity and it was observed that the APOA5 -1131C allele carriers had a reduced risk for obesity (p<0.05). Logistic regression analysis adjusted for age and gender indicated that APOA5 -1131C allele carriage had a protective effect against obesity in the study group (odds ratio: 0.48, 95% confidence interval: 0.29-0.78; p=0.003). In this study, the APOA5 gene polymorphism, one of the genetic factors that may lead to atherosclerotic CAD, was found to be associated with obesity. The APOA5 -1131T>C polymorphism was associated with important risk factors for CAD, obesity and serum lipid levels.